Controlling Nutritional Status (CONUT) Predicts Survival in Gastric Cancer Patients With Immune Checkpoint Inhibitor (PD-1/PD-L1) Outcomes - Chen, Li; Sun, Hao; Zhao, Ruihu; Huang, Rong; Pan, Hongming; Zuo, Yanjiao; Zhang, Lele; Xue, Yingwei; Song, Hongjiang; Li, Xingrui (Frontiers in Pharmacology, 2022)
Objective: The controlling nutritional status (CONUT), based on total lymphocyte count (TL), total cholesterol level (T-CHOL), and serum albumin (ALB), can provide a useful immunological prognostic biomarker for cancer patients. The present study aims to investigate the correlation between CONUT and prognosis in gastric cancer patients receiving immune checkpoint inhibitor (ICI) treatment. Methods: We retrospectively enrolled 146 patients with gastric cancer treated with ICIs (PD-1/PD-L1 inhibitors) from August 2016 to December 2020. The clinicopathologic characteristics were analyzed by Chi-square test or Fisher’s exact test. The Kaplan–Meier and log-rank test were used to calculate and compare progression-free survival (PFS) and overall survival (OS). The prognostic and predictive factors of PFS and OS were identified by univariate and multivariate analyses. A nomogram was developed to estimate 1-, 3-, and 5-year PFS and OS probability. Results: Through the CONUT score, there were 75 (51.37%) patients in the low CONUT group and 71 (48.63%) patients in the high CONUT group. There was a correlation between the CONUT score and age (p = 0.005), pathology (p = 0.043), ALB (p = 0.020), PALB (p = 0.032), and Hb (p = 0.001). The CA724, TNM stage, and treatment (ICIs vs. chemotherapy) were the independent prognostic factors for PFS and OS by multivariate analyses. Patients with high CONUT score had poorer PFS and OS (χ2 = 3.238, p = 0.072, and χ2 = 4.298, p = 0.038). In the subgroup analysis, the patients with high CONUT score were associated with shorter PFS and OS with ICIs or chemotherapy. With the PD-1/PD-L1 positive expression, the patients with high CONUT score had shorter PFS and OS than those with low CONUT score. Furthermore, the patients with high CA724 value were associated with shorter PFS and OS. The toxicity assessment in ICIs or chemotherapy was significantly associated with anemia. The nomograms were constructed to predict the probability of 1-, 3-, and 5-year PFS, and 1-, 3-, and 5-year OS with C-indices of 0.749 and 0.769, respectively. Conclusion: The CONUT, as a novel immuno-nutritional biomarker, may be useful in identifying gastric cancer patients who are unlikely to benefit from ICI treatment.